2023
DOI: 10.1097/apo.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Phacoemulsification in Japanese Patients Receiving First and Revised Second-Generation Trabecular Microbypass Stents

Abstract: Purpose: This study evaluated the effectiveness and safety of first and revised second-generation trabecular microbypass stent insertion [iStent (IS) and iStent inject W (IW)] in cataract surgery. Design: Single-center, retrospective, cohort study. Methods: The study included 176 eyes that received trabecular microbypass stents combined with cataract surgery at the Saitama Red Cross Hospital between September 2017 and September 2021. Patients were divided into IS and IW groups depending on the implant type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Several retrospective have compared iStent with iStent inject. However, our study is valuable owing to the scarcity of studies comparing the outcomes of iStent and inject W [ 15 ]. In addition, few studies have reported on the follow-up results of Inject W beyond one year [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective have compared iStent with iStent inject. However, our study is valuable owing to the scarcity of studies comparing the outcomes of iStent and inject W [ 15 ]. In addition, few studies have reported on the follow-up results of Inject W beyond one year [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study is valuable owing to the scarcity of studies comparing the outcomes of iStent and inject W [ 15 ]. In addition, few studies have reported on the follow-up results of Inject W beyond one year [ 15 ]. The study also examined the safety and factors associated with the success or failure of Inject W. Our study reported some of the first comparative 12-month outcomes of the first- and second-generation trabecular micro-bypass stents, viz.…”
Section: Discussionmentioning
confidence: 99%